Strength and erodibility characteristics of compressed stabilised earth blocks using rice husk ash and lime - Kumar, R. Sathish; Janardhana, Maganti; Kumar, N. Darga (Journal of Structural Engineering, 2024)
Construction of building requires various building materials including burnt clay bricks. When compared to burnt clay bricks, Compressed Stabilised Earth Blocks (CSEBs) have certain advantages as the blocks can be manufactured without burning and by making use of locally available materials and hence reduces the transportation cost as the production can be done at the site. CSEB is considered to be energy efficient and environmental friendly building material. This investigation has evaluated the erodibility characteristics and the effect of varying exposure conditions on the wet compressive strength of CSEBs stabilized with rice husk ash and lime. The CSEBs were sprayed with water at a constant pressure of 1.5 kg/cm² for a period of two hours and the depth of erosion was measured for every 15 minutes. The results of the weathering spray test clearly satisfy the Indian standard code provisions for soil based blocks which reflect the excellent performance of CSEBs stabilised with rice husk ash and lime.